2008
DOI: 10.1088/0953-8984/20/36/365216
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the elastic properties of composite host/guest type crystals

Abstract: The elastic properties of host/guest type composite crystals, with urea as the host and an alkane as the guest, have been studied by Brillouin spectroscopy as a function of hydrostatic pressure. The effect of changing hydrostatic pressure in the range from 0 to 1400 bar on the propagation of acoustic phonons has been determined using three gases—helium, nitrogen and argon—as the pressure-exerting media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…On the basis of measurements for different polarizations of the incident and scattered beams, optimum orientation of the samples was established and for the samples in this orientation the frequency of the phonons was analysed as a function of the hydrostatic pressure applied [12]. The results have shown that with increasing pressure, for the longitudinal phonons propagating in the [0 1 0] direction the Brillouin frequency shift increases, while that of the transversal modes decreases.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of measurements for different polarizations of the incident and scattered beams, optimum orientation of the samples was established and for the samples in this orientation the frequency of the phonons was analysed as a function of the hydrostatic pressure applied [12]. The results have shown that with increasing pressure, for the longitudinal phonons propagating in the [0 1 0] direction the Brillouin frequency shift increases, while that of the transversal modes decreases.…”
Section: Resultsmentioning
confidence: 99%
“…It is a method to investigate viscoelastic behavior of materials by analyzing the peaks' broadening associated with acoustic attenuation in the GHz frequency regime in polymers and other soft materials as a function of temperature (up to few hundred degrees K; Adshead and Lindsay 1982;Takagi et al 2007). Finally, the analysis of the intensity of Brillouin scattering spectra is a method to obtain quantitative information on the photoelastic tensor of materials (e.g., Nelson et al 1972;Vacher and Boyer 1972;Grimsditch and Ramdas 1976;Wallnöfer et al 1994;Mielcarek et al 2008).…”
Section: Brillouin Scattering At Ambient or Near-ambient Conditionsmentioning
confidence: 99%